Acquired resistance to MET kinase inhibition in MET-dependent non-small cell lung cancer cells mediated by a switch to EGFR dependency - McDermott, Ultan (2010)
The MET receptor tyrosine kinase has been implicated in several solid tumor settings, with MET gene amplification present in a subset of patients with epithelial tumors, including non-small cell lung cancer (NSCLC). MET gene amplification also appears to underlie acquired resistance to EGFR kinase inhibitor therapy in ~20% of NSCLC patients that initially respond to such treatment. In vitro studies have demonstrated that cancer cells harboring MET amplification demonstrate striking sensitivity to small molecule selective MET kinase inhibitors, prompting efforts to evaluate such inhibitors in clinical trials. Previous experience with kinase-targeted therapeutics such as the selective tyrosine kinase inhibitors (TKIs) imatinib and erlotinib, in chronic myeloid leukemia and NSCLC, respectively, has revealed that most treatment-responsive patients eventually relapse with drug-resistant disease. Here, we have modeled acquired resistance to the investigational MET kinase inhibitor PF2341066 in MET-amplified NSCLC cell lines to identify specific drug resistance mechanisms that are anticipated in the course of clinical development. Through this analysis, we identified EGFR (epidermal growth factor receptor) pathway engagement as a PF2341066 resistance mechanism in MET-amplified cells following prolonged drug exposure. While combined inhibition of MET and EGFR kinases in MET-dependent NSCLC cells did not detectably enhance their acute PF2341066 sensitivity, this combination dramatically suppressed the eventual emergence of drug-resistant clones following prolonged exposure. Conversely, activating the EGFR pathway with the receptor ligand EGF increased the yield of PF2341066-resistant clones, confirming the significance of this pathway in conferring resistance to MET TKIs. These findings further support an intimate relationship between EGFR and MET signaling pathways in NSCLC, and suggest that a combination treatment strategy with MET and EGFR kinase inhibitors may be beneficial in MET-amplified NSCLC.